Practical Exploration of Integrating Intangible Cultural Heritage into University Curriculum: A Study on the Construction of the School-based Curriculum System of Suixi Lion Dance - Zhang, Hua; Liao, Yanhua (Journal of Educational Research and Policies, 2025)
Against the backdrop of the national strategy to vigorously promote the excellent traditional Chinese culture, integrating intangible cultural heritage systems into the curriculum of colleges and universities has become an important path to deepen cultural education. However, current intangible cultural heritage education in colleges and universities generally suffers from problems such as “fragmentation”, “superficiality”, and the “separation of skills transmission and cultural spirit”. Therefore, this study takes the national-level intangible cultural heritage “Suixi Lion Dance” as a case to explore the construction of a set of referenceable school-based curriculum systems in colleges and universities. Based on the embodied cognition theory and Skilbeck’s situational model, this study first proposes the core concept of “culture as the soul, practice as the body, and innovative development”, and constructs a “three-dimensional integration” content framework around this concept, covering three dimensions: cultural understanding, physical practice, and innovative transformation. Through the implementation path of “curricularization, clubization, and socialization” and combined with a diversified evaluation mechanism, a complete curriculum model is formed. This system aims to break through the limitations of the traditional “technique-only” approach, achieving an organic integration from “knowing the lion” to “dancing the lion” and then to “creating the lion”, promoting the elevation of intangible cultural heritage education from mere skill practice to the inheritance of cultural spirit and the cultivation of innovative ability, in response to the “high-level” requirements of higher education for the cultivation of high-quality, innovative talents. This research not only provides theoretical references and practical solutions for the “living inheritance” and “creative transformation” of “Suixi Lion Dance” and similar physical intangible cultural heritage projects in colleges and universities, but also contributes a replicable curriculum model for local colleges and universities to develop distinctive paths based on regional cultural resources and cultivate high-quality applied talents.